Psychology in Caring for the Elderly - Chuanchom, Jirat; Korlertvorapong, Passarin; Pogard, Patumporn (Rajapark Journal, 2024)
This academic article aims to present the application of psychology to the elderly. The aging society has become an important issue in Thai society because Thailand is about to enter an aging society. Entering the elderly will undergo physical changes such as illness and deterioration of various systems in the body. As a result, it causes a feeling that self-worth has decreased due to the changes that have occurred. It will be born from the psychological side. As follows: 1) There are serious events that affect the feelings, such as the loss of a loved one; and 2) lack of care from the family. Family members should try to adapt to understand people at this age. Activities that are suitable for the elderly so that they can live happily. Activities to promote knowledge for the elderly Traditional and religious activities and exercise activities. In addition, it was found that the elderly have adapted to maintain their mental and social well-being by participating in community activities and religious beliefs. In addition, promoting and creating a sense of self-worth for the elderly or having a goal in life is considered important for living. The consequences of caring for the elderly affect their physical and mental health. It consists of happiness, enjoyment, gracefulness, enlightenment, and peace.